Safety Profile of Monoclonal Antibody Compared With Traditional Anticancer Drugs: An Analysis of Henan Province Spontaneous Reporting System Database - Jiao, Zhiming; Wang, Ganyi; Feng, Zhanchun; Yan, Ziqi; Zhang, Jinwen; Li, Gang; Wang, Qianyu; Feng, Da (Frontiers in Pharmacology, 2022)
Introduction: Monoclonal antibody (mAb) is an important treatment option for cancer patients and has received widespread attention in recent years. In this context, a comparative safety evaluation of mAb and traditional anticancer drugs in real-world is warranted. Methods: ADR reports submitted to Henan Adverse Drug Reaction Monitoring Center from 2016 to 2020 for individuals taking antineoplastic drugs were included. Data were analyzed with respect to demographic characteristics, disease types, polypharmacy, past history of ADRs, system organ class, name of suspected drugs per ADR report, severity, result, impact on the primary disease, and biosimilars. Results: A total of 15910 ADR reports related to antineoplastic drugs were collected, 575 (3.61%) cases were related to mAb. Female had more reports of ADRs than male. The ADRs of non-mAbs mainly occurred in 1 - 3 days after injection (4929, 32.15%), whereas those of mAbs mainly occurred on the same day (297, 51.65%). Serious ADRs accounted for 30.26% (n = 174) of mAb-related reports and 34.46% (n = 5285; four death cases) of non-mAb-related reports, respectively. A total of 495 (86.08%) reports were related to the branded drugs of mAb. Female, aged 60 to 79 years, had a single disease, had no history of adverse reactions and had received treatment regimens were less likely to be affected by the primary disease after receiving mAb therapy. The signal mining method produced 14 signals, only Sintilimab-Hepatic failure was off-label ADR. Conclusion: This study partly confirmed the safety profile of mAb. It is unlikely to affect groups such as the elderly, individuals with a single disease, and individuals who have had no adverse reactions in the past. Combined drugs have little effect on the primary disease. By conducting signal mining method, 14 signals were produced, and only one of them was off-label ADR.